Production of Blast resistance and good grain quality rice lines by anther culture and molecular markers - Bay, Phan Thi; Hanh, Dao Thi; Lien, Quach Thi; Muoi, Le Thi; Thanh, Nguyen Duc (Academia Journal of Biology, 2015)
In recent years, the use of the biotechnology for rice breeding has gained considerable progress. The anther culture and markers-aiding the selection for rice breeding are the most promising techniques. In this paper, the preliminary results on the production of blast resistance and good grain quality rice lines by these techniques are presented. 480 green plants from 32 calluses were obtained by the anther culture technique. Among them, 195 plants from 15 calluses (47%) were haploid and 285 plants from 17 calluses (53%) were double haploid plants. Twelve selected lines were analyzed by using molecular markers linked to blast resistance gene and grain quality. Four blast resistance and good grain quality rice lines (HPMD4, HPMD6, HPMD9, HPMD13) were selected for further genetically analyses and selection.